Forms of Understanding for XAI-Explanations - Buschmeier, Hendrik; Buhl, Heike M.; Kern, Friederike; Grimminger, Angela; Beierling, Helen; Fisher, Josephine Beryl; Groß, André; Horwath, Ilona; Klowait, Nils; Lazarov, Stefan Teodorov; Lenke, Michael; Lohmer, Vivien; et al. (Cognitive Systems Research)
Explainability has become an important topic in computer science and artificial intelligence, leading to a subfield called Explainable Artificial Intelligence (XAI). The goal of providing or seeking explanations is to achieve (better) ‘understanding’ on the part of the explainee. However, what it means to ‘understand’ is still not clearly defined, and the concept itself is rarely the subject of scientific investigation. This conceptual article aims to present a model of forms of understanding for XAI-explanations and beyond. From an interdisciplinary perspective bringing together computer science, linguistics, sociology, philosophy and psychology, a definition of understanding and its forms, assessment, and dynamics during the process of giving everyday explanations are explored. Two types of understanding are considered as possible outcomes of explanations, namely enabledness, ‘knowing how’ to do or decide something, and comprehension, ‘knowing that’ – both in different degrees (from shallow to deep). Explanations regularly start with shallow understanding in a specific domain and can lead to deep comprehension and enabledness of the explanandum, which we see as a prerequisite for human users to gain agency. In this process, the increase of comprehension and enabledness are highly interdependent. Against the background of this systematization, special challenges of understanding in XAI are discussed.
Keywords: understanding; explaining; explanations; explainable; AI; interdisciplinarity; comprehension; enabledness; agency

The role of interactive gestures in explanatory interactions - Lohmer, Vivien; Kern, Friederike (Second International Multimodal Communication Symposium (MMSYM) - Book of Abstract)
Keywords: gesture; explanations; conversation analysis

Changes in the topical structure of explanations are related to explainees’ multimodal behaviour - Lazarov, Stefan Teodorov; Biermeier, Kai; Grimminger, Angela (Interaction Studies)
Everyday explanations are interactive processes with the aim to provide a less knowledgeable person with reasonable information about other people, objects, or events. Because explanations are interactive communicative processes, the topical structure of an explanation may vary dynamically depending on the immediate feedback of the explainee. In this paper, we analyse topical transitions in medical explanations organised by different physicians (explainers) related to different forms of multimodal behaviour of caregivers (explainees) attending an explanation about the procedures of an upcoming surgery of a child. The analyses reveal that explainees’ multimodal behaviour with gaze shifts (and particularly gaze aversion) can predict a transition from an elaborated topic to a new one, whereas explainees’ forms of multimodal behaviour with static gaze cannot be related to changes of the topical structure.
Keywords: explanations; multimodal behaviour; elaborations; conditional probabilities

A Prototype of an Interactive Clinical Decision Support System with Counterfactual Explanations - Liedeker, Felix; Cimiano, Philipp
We describe a prototype of a Clinical Decision Support System (CDSS) that provides (counterfactual) explanations to support accurate medical diagnosis. The prototype is based on an inherently interpretable Bayesian network (BN). Our research aims to investigate which explanations are most useful for medical experts and whether co-constructing explanations can foster trust and acceptance of CDSS.
Keywords: Explainable AI; Clinical decision support; Bayesian network; Counterfactual explanations

Explaining the Technical Artifact Quarto!: How Gestures are used in Everyday Explanations - Lohmer, Vivien; Terfloth, Lutz; Kern, Friederike (First International Multimodal Communication Symposium - Book of Abstract)
Keywords: gesture; dual nature; explanations; architecture; relevance